Analisis Kesalahan Berbahasa Arab - Yolanda Selviana (Aphorisme: Journal of Arabic Language, Literature, and Education, 2021)
This study aims to describe the analysis of insya’ writing errors done by Class VIII students of MTsN XII Madiun. The research method used was qualitative. The research data were in the form of insya’ writing errors done by Class VIII students of MTsN XII Madiun. Data collection techniques were observation, interviews, and documentation. Data analysis was performed by collecting insya’ writing errors, identifying insya’ writing errors, explaining insya’ writing errors, and evaluating insya’ writing errors. The results of the study found insya’ writing errors done by Class VIII students of MTsN XII Madiun lead to grammatical aspects (phonology, morphology, and syntax), addition, and arrangement errors. Then, the evaluation of Arabic language learning that must be done is to deepen the study of Arabic grammar, practice consistently, and choose the right learning method.